Critical transitions in chronic disease: transferring concepts from ecology to systems medicine. (August 2015) - Trefois, Christophe; Antony, Paul MA; Goncalves, Jorge; Skupin, Alexander; Balling, Rudi
Graphical abstract: Highlights: Critical transitions (CT) can occur in complex diseases. Early warning signals (EWS) such as changes in variance can occur before such CTs. EWS might be useful in disease prediction and diagnosis. Abstract : Ecosystems and biological systems are known to be inherently complex and to exhibit nonlinear dynamics. Diseases such as microbiome dysregulation or depression can be seen as complex systems as well and were shown to exhibit patterns of nonlinearity in their response to perturbations. These nonlinearities can be revealed by a sudden shift in system states, for instance from health to disease. The identification and characterization of early warning signals which could predict upcoming critical transitions is of primordial interest as prevention of disease onset is a major aim in health care. In this review, we focus on recent evidence for critical transitions in diseases and discuss the potential of such studies for therapeutic applications.